2015
DOI: 10.1063/1.4919664
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Salt-induced water orientation at a surface of non-ionic surfactant in relation to a mechanism of Hofmeister effect

Abstract: Development of single-channel heterodyne-detected sum frequency generation spectroscopy and its application to the water/vapor interface

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This means that the net orientation of water at neutral lipid interfaces is highly dependent on the chemical structure of the lipid headgroup unlike the charged lipid interfaces where the water orientation is determined solely by the charge of the lipid headgroup independently from the chemical structure of the headgroup. In fact, water orientation at a different neutral lipid (monomyristolein) monolayer was previously reported to be essentially H-down, 50 supporting the crucial importance of the headgroup structure in determining net water orientation at neutral lipid interfaces. As for the origin of the difference between ceramide and monomyristolein, we speculate that intramolecular H-bond within the headgroup is less significant in monomyristolein.…”
Section: ■ Introductionmentioning
confidence: 77%
“…This means that the net orientation of water at neutral lipid interfaces is highly dependent on the chemical structure of the lipid headgroup unlike the charged lipid interfaces where the water orientation is determined solely by the charge of the lipid headgroup independently from the chemical structure of the headgroup. In fact, water orientation at a different neutral lipid (monomyristolein) monolayer was previously reported to be essentially H-down, 50 supporting the crucial importance of the headgroup structure in determining net water orientation at neutral lipid interfaces. As for the origin of the difference between ceramide and monomyristolein, we speculate that intramolecular H-bond within the headgroup is less significant in monomyristolein.…”
Section: ■ Introductionmentioning
confidence: 77%
“…There have been many developments in measuring phase-resolved spectra of the much narrower spectral features in the C-H stretching vibration region and protein amide band region, etc. [79,[177][178][179][180]. However, as discussed in Section 3.2, when there are non-negligible bulk contributions, such as the (3) χ mechanism from charges surfaces/interfaces, the notion that the imaginary SFG-VS spectrum contains only the absorptive term of the susceptibility can no longer be taken for granted, and the interpretation of the SFG-VS imaginary spectra based only on this notion needs to be cautioned and carefully examined [29], particularly for charged aqueous surfaces/interfaces [92,181] and aqueous surfaces/interfaces of accumulated ions [93,182].…”
Section: Accuracy Of Phase Reference In Phase-resolved Sfg-vsmentioning
confidence: 99%
“…They also found that a positive Im χ (2) band appears around 3600 cm −1 , and it indicates the presence of weakly interacting water molecules with net H-up orientation in the hydrophobic region of the lipid monolayer interface. The orientation of water molecules at a nonionic surfactant (monomyristolein)/water interface and its water orienting capability were investigated with HD-SFG spectroscopy by Ishibashi et al 40 They found that water molecules at the interface are oriented with their hydrogen atoms pointing to the bulk. With SFG, water molecules at the lipid interfaces with distinct hydrogen-bonding sites are experimentally observed and the structure of water molecules as well as their net orientation can be directly determined.…”
Section: ■ Introductionmentioning
confidence: 99%